Structural Identifiability Applied to a Heat Transfer System - Sanz Bermejo, Javier; Ramírez Laboreo , Édgar; Sagüés Blázquiz, Carlos (Jornada de Jóvenes Investigadores del I3A, 2022)
Identifiability is an essential property of a dynamical model whose study should be addressed before performing any parameter estimation procedure. In this work, we study the structural identifiability of a heat transfer system by making use of the local state isomorphism theorem for two scenarios based on the available experimental measurements.